An assessment of recruitment and selection practices among Banks in Ghana. A case study of Asokore Rural Bank Limited and Zenith Bank in the Kumasi Metropolis. - Owusu-Dapaah, John (2015)
A thesis submitted to the Department of Managerial Sciences, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Business Administration.